Modelling and characterisation ultrasonic phased array transducers for pipe inspections. (December 2022) - Hampson, Rory; Zhang, Dayi; Gachagan, Anthony; Dobie, Gordon
Abstract : Nuclear pipes require regular inspection to prevent critical damage and extend their safe working lifetime. Ultrasonic inspection using phased array transducers is a Non-Destructive Testing (NDT) method used to monitor the condition of pipes, providing internal integrity information using multiple small transducer elements. This grants a controllable ultrasonic beam that provides more detail than a conventional single element transducer. This paper presents a hybrid simulation model to characterise phased array ultrasonic transducers for pressure pipe inspections. The paper focuses on identifying defects on pipe surfaces, which have total propagation path lengths in the order of 170 ultrasound wavelengths. Simulating inspections with such large path lengths is challenging due to unreliable results from numerical dispersion errors in large finite element models. The model presented here combines the benefits of finite element modelling with analytical extrapolation to overcome the issue of large propagation distances. A practical experiment demonstrates and verifies that the hybrid simulation model matches real world inspections. Inspection accuracy was quantified using the hybrid simulation model over frequency (5, 7.5 and 10 MHz) and number of elements (8, 16 and 32) to inspect two defect shapes (rectangular and V-shape). The 10 MHz transducer showed the highest resolution for the depth measurement, while the 5 MHz transducer presented the strongest penetration to inspect the defects on the pipe's outer surface. The largest aperture transducer, 32 elements, brought about the most accurate defect size measurement. This work serves to inexpensively guide the selection and later deployment of phased array inspection tools in nuclear pipe defect detection and monitoring. Highlights: A novel hybrid simulation model representing high frequency ultrasonic phased array inspections to produce high-resolution TFM images. Novel surface imaging algorithms measure the width and the depth of defects on the pipe surface. The novel hybrid model and surface imaging algorithms are validated on practical examples. Quantification of the impact of the transducer's element number and excitation frequency on inspection accuracy.